Influence of Temperature and Pressure on Gas Emission Due to Crack Propagation in Coal-Mines: An Experimental Study - Man-Chao He (Canadian Institute of Mining, Metallurgy and Petroleum, 2013)
One of the critical problems involved in deep coalmines is unusual gas emissions. Many researchers agree that there is a relationship between coal gas emissions and geological features such as tectonics or geological disturbances, gas content, properties of the coal and rock and the mininginduced stress state in the coal seam and rock. Thus, the present paper intends to investigate complex mechanical phenomena during the process of gas emission in underground coal-mines. A program of laboratory testing was undertaken to study the effects of temperature and pressure on mechanisms of gas emission. It must be noted that this paper describes new techniques developed to simultaneously measure deformation and gas pressure, as well as flux during the test, taking the characteristics of gas transport into consideration under certain temperature and pressure conditions. The results indicate that under certain temperature and pressure conditions, gases adsorbed to coal start to desorb, and increase the pore pressure. High pressure gases entering coal fractures can generate high tensile stresses near the crack tips, leading to crack propagation and coalescence, which in turn can cause the specimen to dilate. From the experimental viewpoint, these test results may help us discern why mining seismic events can trigger gas emissions.